2016
DOI: 10.5005/jp-journals-10024-1863
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Various Nutritional Parameters in Geriatric Patients Who underwent Different Prosthodontic Treatments

Abstract: Background: Some relation exists between oral and general health with progressive aging. Certain risk factors are common between oral and systemic diseases. Absence of teeth also affects the oral health by altering the quality of life. Hence, the nutritional changes occurring in elderly patients following prosthodontic rehabilitation are evaluated. Materials and methods:A total of 250 patients who underwent prosthodontic treatment for missing teeth were included for the study. Twice measurement of nutritional … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…While comparing the mean calcium intake by the patients, all the groups showed a significant increase in the mean values of the calcium. The current study results were in correlation with the results of Aneja et al, 14 who also observed significant increase in calcium intake on denture wearers. This might be due to significance increase in uptake of fruits, vegetables, and salads after prosthetic rehabilitation.…”
Section: Discussionsupporting
confidence: 92%
“…While comparing the mean calcium intake by the patients, all the groups showed a significant increase in the mean values of the calcium. The current study results were in correlation with the results of Aneja et al, 14 who also observed significant increase in calcium intake on denture wearers. This might be due to significance increase in uptake of fruits, vegetables, and salads after prosthetic rehabilitation.…”
Section: Discussionsupporting
confidence: 92%
“…388 As suggested in studies conducted previously, the importance of high-quality prosthodontic treatment for the nutrition and improvement of the general health of geriatric patients has been confirmed in several studies. Aneja et al 389 showed in a study cohort of 250 patients treated with different types of prostheses (complete denture, partial denture, fixed prosthesis) that complete dentures are a risk factor for impaired nutrition in the elderly, nondentate patients (parameters included body mass index, protein, iron, and carbohydrate values) compared with dentate patients. However, Han et al 390 and Goel et al 391 published concurring prospective, long-term findings that elderly patients with dentures (complete, partial) have improved nutritional status compared with patients with edentulism, which highlights the importance of prosthetic rehabilitation regardless of the age group.…”
Section: Oral Medicine and Oral And Maxillofacial Surgerymentioning
confidence: 99%